The family of 14‐3‐3 proteins and specifically 14‐3‐3σ are up‐regulated during the development of renal pathologies. Issue 9 (28th June 2018) - Rizou, Myrto; Frangou, Eleni A.; Marineli, Filio; Prakoura, Niki; Zoidakis, Jerome; Gakiopoulou, Harikleia; Liapis, George; Kavvadas, Panagiotis; Chatziantoniou, Christos; Makridakis, Manousos; Vlahou, Antonia; Boletis, John; et al.
Abstract: Chronic kidney disease, the end result of most renal and some systemic diseases, is a common condition where renal function is compromised due to fibrosis. During renal fibrosis, calreticulin, a multifunctional chaperone of the endoplasmic reticulum (ER) is up‐regulated in tubular epithelial cells (TECs) both in vitro and in vivo. Proteomic analysis of cultured TECs overexpressing calreticulin led to the identification of the family of 14‐3‐3 proteins as key proteins overexpressed as well. Furthermore, an increased expression in the majority of 14‐3‐3 family members was observed in 3 different animal models of renal pathologies: the unilateral ureteric obstruction, the nephrotoxic serum administration and the ischaemia‐reperfusion. In all these models, the 14‐3‐3σ isoform (also known as stratifin) was predominantly overexpressed. As in all these models ischaemia is a common denominator, we showed that the ischaemia‐induced transcription factor HIF1α is specifically associated with the promoter region of the 14‐3‐3σ gene. Finally, we evaluated the expression of the family of 14‐3‐3 proteins and specifically 14‐3‐3σ in biopsies from IgA nephropathy and membranous nephropathy patients. These results propose an involvement of 14‐3‐3σ in renal pathology and provide evidence for the first time that hypoxia may be responsible for its altered expression.